Photoluminescence of Ca10V6O25:Eu3+: A theoretical and experimental approach - Teixeira, Mayara M.; Pinatti, Ivo M.; Laranjeira, José A.S. [UNESP]; Fabris, Guilherme S.L.; Teodoro, Marcio D.; Rosa, Ieda L.V.; Simões, Alexandre Z. [UNESP]; Andrés, Juan; Sambrano, Julio R. [UNESP]; Longo, Elson (Elsevier, 2024)
Ca10−xV6O25:xEu (x = 0%, 0.5%, 1%, 2%, 4%, and 8%) samples were synthesized by the microwave-assisted hydrothermal method at low temperature and short time. The corresponding structures were investigated by X-ray diffraction with Rietveld refinement, Raman spectra, and field emission scanning electron spectroscopy. Eu3+ cations incorporated in Ca10V6O25 provoke a structural disorder with concomitant changes in the morphology. In order to complement and rationalize the structural and electronic effects, computational simulations via density functional theory were employed to rationalize the structural and electronic effects on the constituent clusters of Ca10V6O25 after the Eu3+-doping process. The photoluminescence emission spectra showed characteristic f-f transitions ascribed to Eu3+ cations and broadband related to Ca10V6O25. Besides, the matrix-supported a higher percentage of 8% without the quenching effect. These results indicate the potential applications of the obtained materials in optical devices.
Keywords: Ca10V6O25; Calcium Vanadate; DFT calculations; Eu3+; Photoluminescence